Nazi Policy of Tourism in Central Europe - Ivan Jakubec (Historicka Sociologie, 2023)
The primary focus of this paper is on the period of tourism from 1938/39 to 1945. The intention of this paper is to present and explain the reasons and consequences of the implementation of organizational changes, as well as the impacts of the integration of tourism into the staterun economy of Nazi Germany. In this context, we evaluated the specifics of the development of tourism areas of the former Czechoslovak state (the Sudetenland, the Protectorate of Bohemia and Moravia, Slovakia). It turned out that even during the war, tourism, despite all the restrictions (legislative, territorial, time, transport, etc.) did not disappear, except in areas where war operations were taking place, and its management became an integral part of the war economy. The explanation can be seen based on the studied materials in the multilayered nature of this part of the national economy and its broad social scope. The paper is based on the study of archival unpublished materials from Czech and foreign archives and literature. The basic method used is the historical-critical method supplemented by a comparative, direct and indirect approach with an effort to capture the overall changes in the field of tourism during the war.